2017
DOI: 10.21608/jpp.2017.41115
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Potassium Silicate Compound as Foliar Application on the Growth, Yield and Grains Quality of GIZA 179 Rice Cultivar.

Abstract: Two field experiments were conducted at the Experimental Farm of Rice Research Department (R.R.D.), Sakha, Kafrelsheikh, Egypt during 2015 and 2016 seasons. In order to examine the impact of potassium silicate compound as foliar application on the growth, yield and grains quality of Giza 179 rice cultivar. A randomized complete block design (R.C.B.D.) with four replications was used in the two seasons. Foliar applications of potassium silicate, at the rate of control (without potassium silicate), 0.5%, 1.0%, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
3
2
0
Order By: Relevance
“…Silica may increase IAA and GA3 production while decreasing ABA production. The current findings are in a good agreement with those reported by Wissa (2017) and Aurangzaib et al, (2021). The results also obtained in the present investigation concerning the effect of K-humate, the favorable effects of humic acids on yield components could be attributed to increased amounts of endogenous cytokinin and auxins, which would likely lead to higher yields (Salem et al, 2017).…”
Section: Grain Yield Straw Yield Biological Yield Ton H -1 and Harves...supporting
confidence: 92%
“…Silica may increase IAA and GA3 production while decreasing ABA production. The current findings are in a good agreement with those reported by Wissa (2017) and Aurangzaib et al, (2021). The results also obtained in the present investigation concerning the effect of K-humate, the favorable effects of humic acids on yield components could be attributed to increased amounts of endogenous cytokinin and auxins, which would likely lead to higher yields (Salem et al, 2017).…”
Section: Grain Yield Straw Yield Biological Yield Ton H -1 and Harves...supporting
confidence: 92%
“…This corroborated the findings by [63,64]. According to a similar study by [12], addition of silica at 120 kg/ha showed the maximum growth and yield of rice.…”
Section: Effect Of Silicon Fym and Inorganic Fertilizers On Yield Par...supporting
confidence: 89%
“…Organic and inorganic fertilizers along with silicon increased the uptake of nutrients, water use efficiency, and other physiological processes of plants, which increased plant height as evidenced by [12] in rice. The results in terms of more leaves per plant and a higher leaf area index were corroborated with the findings of [28,29] in broccoli and [25] while working with cauliflower.…”
Section: Treatments Curd Diameter (Cm)mentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in silica levels led to the plants being more erect and reduced the self-shading of lower leaves of the canopy, which made the plants more photosynthetic efficient and better able to exploit the space available to intercept solar radiation, consequently increasing leaf area index, dry matter, and plant height. A similar result was found by Zanão Júnior et al (2010), De Oliveira et al (2016), Wissa. (2017 and Mikhael et al (2018).…”
Section: A-growth Characteristicssupporting
confidence: 87%